Correlates of Program Success and Recidivism among Participants in an Adult Pre-Arrest Diversion Program - Kopak, Albert M. (American journal of criminal justice, 2017)
Adult pre-arrest diversion, also known as “deflection,” programs have great potential to change the way the criminal justice system currently operates. One defining feature of these programs is that they offer eligible adults the opportunity to avoid a formal criminal arrest record and all of the negative consequences that are associated with an arrest. The current study provides an assessment of factors related to successful program completion and post-program recidivism for participants in the Pre-Arrest Diversion/Adult Civil Citation (PAD/ACC) program in Leon County, Florida. Behavioral assessment and formal arrest data were drawn from 854 adults who participated in the program between March 2013 and June 2016. Adults undergo a comprehensive behavioral health assessment which utilizes the Global Assessment of Individual Needs (GAIN–SS). Several behavioral health indicators were associated with program outcome measures, which included successful program completion and post-program arrest. Participants with greater propensity for crime or violence, elevated levels of behavioral problems, and symptoms of a substance use disorder, including a positive drug screen, were more likely to fail to complete the program. Greater indications of behavioral problems and positive drug screen results were also significantly associated with a higher probability of post-program arrest. These results contribute to the lean knowledge related to the performance of these expanding programs, and they also have direct implications for the refinement of the PAD/ACC program.